Natural variation in host-finding behaviour of gastropod parasitic nematodes (Phasmarhabditis spp.) exposed to host-associated cues. (24th February 2021) - Cutler, J.; Rae, R.
Abstract: The gastropod parasitic nematode Phasmarhabditis hermaphrodita has been formulated into a successful biological control agent (Nemaslug ®, strain DMG0001) used to kill slugs on farms and gardens. When applied to soil, P. hermaphrodita uses slug mucus and faeces to find potential hosts. However, there is little information on what cues other species of Phasmarhabditis ( P. neopapillosa and P. californica ) use to find hosts and whether there is natural variation in their ability to chemotax to host cues. Therefore, using chemotaxis assays, we exposed nine wild isolates of P. hermaphrodita, five isolates of P. neopapillosa and three isolates of P. californica to mucus from the pestiferous slug host Deroceras invadens, as well as 1% and 5% hyaluronic acid – a component of slug mucus that is highly attractive to these nematodes. We found P. hermaphrodita (DMG0010) and P. californica (DMG0018) responded significantly more to D. invadens mucus and 1% hyaluronic acid than other strains. Also, P. hermaphrodita (DMG0007), P. neopapillosa (DMG0015) and P. californica (DMG0017) were superior at locating 5% hyaluronic acid compared to other isolates of the same genera. Ultimately, there is natural variation in chemoattraction in Phasmarhabditis nematodes, with some strains responding significantly better to host cues than others.